KESEJAHTERAAN PSIKOLOGIS PADA PEREMPUAN DEWASA AWAL YANG MEMILIKI PENGALAMAN KEKERASAN EMOSIONAL - Verizka, Annisa; Kertamuda, Fatchiah Ekowaty (Inquiry: Jurnal Ilmiah Psikologi, 2020)
Violence against women and children become an issue in both western and eastern countries, the abuser may come from parents, caregivers, and spouses. Emotional abuse is one of the hardest to recognize because the signs are not visible in the victims, but the impact itself can interfere with one’s development. Emotional abuse can have an effect on one's psychological well-being. The purpose of this study is to describe psychological well-being in early adult that experience emotional abuse during childhood and adolescence affects. The method of this research is case study qualitative research, the subject of the research is a 22 years old early adult woman and three informants. Technique sampling was used nonprobability sampling technique. Data collection method was interviewe. Based on the result of this research, it can be concluded from six dimension, there are dimensions go well such as positive relationship with others, purpose in life, and personal growth. While in other dimensions, such as self-acceptance, autonomy, and environmental mastery are still in the process of achieving.